2019
DOI: 10.31382/eqol.201202
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of a Serbian version of the State-Trait Anxiety Inventory X-2

Abstract: Given that anxiety is a significant individual disposition that affects sports performance, this study aimed to verify the latent variables obtained by the State – Trait Anxiety Inventory X-2, and to compare the obtained factor solutions with the proposed model of latent variables. The second aim refers to the presentation of the results of the questionnaire State – Trait Anxiety Inventory X-2 answered by Serbian male and female handball players. The research was conducted on a sample of 170 respondents, 99 ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Meanwhile, genetic factors obviously regulate and contribute to the difference in amylose content. Following Jakšić et al (2020) research, the Wx gene genetically controls amylose content by encoding a waxy protein (starch synthase bound to granules). The amylose content which is controled by amylose synthesis and regulated by Waxy (Wx) (LOC_Os06g04200) encoding Granule-Bound Starch Synthase I (GBSSI).…”
Section: Starch Content and Amylosementioning
confidence: 99%
“…Meanwhile, genetic factors obviously regulate and contribute to the difference in amylose content. Following Jakšić et al (2020) research, the Wx gene genetically controls amylose content by encoding a waxy protein (starch synthase bound to granules). The amylose content which is controled by amylose synthesis and regulated by Waxy (Wx) (LOC_Os06g04200) encoding Granule-Bound Starch Synthase I (GBSSI).…”
Section: Starch Content and Amylosementioning
confidence: 99%
“…Research on gender differences in athletes’ mental skills shows inconsistent data. Namely, although some studies indicate significant gender differences in the degree of emotional regulation in favor of male handball players (e.g., Kristjánsdóttir et al, 2018 ), no gender differences in the degree of anxiety as a personality trait were found in the sample of Serbian male and female handball players, and male and female Serbian handball players were found to achieve average scores on anxiety as a personality trait ( Jakšić et al, 2020 ). Some studies have found that female football players react and perceive more intense stress and that they experience less control in stressful situations ( Kaiseler et al, 2012 ).…”
Section: Introductionmentioning
confidence: 97%